Analyze the Implementation of Remuneration an Islamic Perspective at Supermarket Sakinah Surabaya - Istiasih, Shitny Dwi; Manzilati, Asfi; Muljaningsih, Sri (AIBPM Publisher, 2023)
This study aims to analyze the implementation of remuneration from an Islamic perspective at Sakinah Supermarket Surabaya. The type of research that is appropriate is qualitative research. The approach used in this research is the case study method. Data collection was carried out through the stages of observation, interviews, and documentation. After data collection, data interpretation and validation were carried out. The results of this study indicate that the system and principles of wages at Sakinah Supermarket are by several Islamic principles. Remuneration is not only given in the form of money but also emphasized on support services and heart-to-heart relationships between employees. In addition, employees make work a part of worship. This can be seen from the routine activities in the form of halaqah and ease of worship. Islamic principles that have been implemented, such as fair, transparent, and equal. This study found that the wages received are a form of reciprocity for work and behavior at work. So that workers can carry out all the provisions of the company properly and precisely. Meanwhile, employers can provide opportunities for workers to be able to negotiate regarding the wages they will receive to create decent and fair wages for workers.